Christianity according to the Wesleys : the Harris Franklin Rall lectures, 1954, delivered at Garrett Biblical Institute, Evanston, Illinois - Hildebrandt, Franz, 1909-1985. (Grand Rapids, Mich. : Baker Books, 1996)
Though known for their practical theology, as theologians proper John and Charles Wesley have historically been overlooked. This introduction to the theological legacy of the Wesley brothers remedies this oversight. In four chapters originally presented as the Harris Franklin Rall Lectures at Garrett-Evangelical Theological Seminary, Franz Hildebrandt explores the summary aspects of Christianity in the theology of the Wesleys: scriptural, practical, missionary, and catholic. Their sermons, notes on the New Testament, and hymns form the basic source of research, along with numerous excerpts from their letters and journals. Hildebrandt looks at contemporary Methodism in the light of its historic foundation and assesses the teaching of the Wesleys in the light of the New Testament.
"A Labyrinth book."
Includes bibliographical references and indexes.
Keywords: Wesley, John, -- 1703-1791.; Wesley, Charles, -- 1707-1788.; Methodist Church -- Doctrines -- History -- 18th century; Methodist Church -- Doctrines